The Use of Google Scholar as a Literature Search Tool in Writing Theses for Islamic Education Students - Oktaviana, Alda; Alda Oktaviana; Baldi Anggara; Alihan Satra; Fajriansyah, Kautsar (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2026)
This study aims to describe the utilization of Google Scholar by students who are currently writing their theses in the Islamic Education Study Program (PAI) at UIN Raden Fatah Palembang in searching for and selecting literature for thesis writing. The research employed a qualitative descriptive approach with data collected through interviews, observation, and documentation involving students who are writing their theses, the head of the study program, the head of thesis supervision, and Islamic Education (PAI) lecturers. Data were analyzed using Miles and Huberman’s interactive model. The findings reveal that Google Scholar has become the primary academic search tool for students, particularly in writing the literature review (Chapter II) and methodology sections of their theses. Its ease of access, wide coverage of journals, proceedings, theses, and dissertations, and user-friendly features make it highly beneficial. However, several challenges remain, including limited digital literacy, unstable internet connections, difficulties in formulating keywords, and restricted access to paid journals. Supporting factors include the availability of campus internet facilities, guidance from lecturers, and students’ motivation to complete their theses. This study contributes to illustrating the development of academic digital literacy within the context of Islamic higher education. Furthermore, it emphasizes the importance of training in advanced search strategies to optimize the use of Google Scholar. Future research could adopt a quantitative approach to measure the effectiveness of Google Scholar in improving thesis quality and to compare it with other academic database.